DINAMIKA KOMUNITAS DAN INTERAKSI TROFIK SERANGGA PREDATOR PADA AGROEKOSISTEM PADI SAWAH DI PIDIE, ACEH: FONDASI PENGELOLAAN HAMA TERPADU BERKELANJUTAN - Aidil Amar; Diah Fridayati; Tengku Dhean; Mariana Mariana (JURNAL AGROTROPIKA, 2026)
Rice paddy agroecosystems serve as habitat for diverse predatory insect communities that play a critical role in natural pest regulation. This study aimed to analyze the community structure and trophic interaction patterns of predatory insects in the irrigated rice agroecosystem of Gampong Gintong, Grong-Grong District, Pidie Regency, Aceh. Sampling was conducted during three rice growth phases (35, 45, and 55 days after transplanting/DAT) using pitfall traps, yellow pan traps, and sweep nets in five 20×20 m observation plots. A total of 1,468 individual predatory insects were collected, representing 30 families and 7 orders. Formicidae dominated the assemblage at 79.77% of total individuals with stable abundance throughout the growing season. The Shannon-Wiener diversity index (H') ranged from 0.7624 to 0.9275, indicating low to moderate diversity with no significant differences among phases (p = 0.075). In contrast, Simpson's dominance index (C) and Pielou's evenness index (E) differed significantly among growth phases (p < 0.01), reflecting progressive Formicidae dominance associated with canopy development. Sørensen similarity indices (Cs = 0.5882–0.7222) confirmed high stability of the core predator assemblage across all phase comparisons. Trophic network reconstruction identified ten key predator families operating across three distinct vertical zones with complementary diurnal-nocturnal activity patterns. These findings highlight the importance of vegetated refugia conservation at field bunds and reduction of broad-spectrum insecticide use as a foundation for sustainable integrated pest management (IPM).